Biomaterials Physics and Chemistry - New Edition - Pignatello, Rosario; Musumeci, Teresa (IntechOpen, 2018)
This contribution book collects five among reviews and original articles from eminent experts working in the interdisciplinary area of biomaterial synthesis and application. From their direct and recent experience, the readers can access the novel and ongoing potentialities of different synthetic and engineered biomaterials. Contributions reflect the fundamental studies, with a particular attention to the physico-chemical mechanical characterization of biomaterials, along with biocompatibility studies and potential clinical use. After an introductory chapter on the question of storage stability for biomaterial-based devices and products and for polymeric nanomedicines, a first review deals with the use and commercial sources of hydroxyapatite in tissue engineering and other biomedical applications. A study follows on optical fiber laser marking on the properties of stainless steel in implant manufacturing. Two other reviews, respectively, focused on the approaches to prevent or treat the effects of calcification that occurs in vivo on biomaterial-based implants and on the encapsulation of pancreatic islet cells for the treatment of type I diabetes will be presented. Finally, an overview on the physical bases and application in biomaterial science of the spray-drying process will close the volume. This setting will allow to achieve a general view of how classical and novel biomaterials can be applied, along with the methodologies necessary to design, develop, and characterize them, without the restrictions necessarily imposed by industrial or profit concerns. Readers will be apprised about the methodologies used to develop biomaterials possessing the physical and biological properties needed for specific medical and clinical applications.